2019
DOI: 10.1021/acs.macromol.9b02298
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-Ligand Approach to Palladium-Catalyzed Direct Arylation Polymerization: Synthesis of Donor–Acceptor Polymers Containing Unsubstituted Bithiophene Units

Abstract: The combined use of P(2-MeOC 6 H 4 ) 3 (L1) and TMEDA as ligands effectively prevents defect formation in palladiumcatalyzed direct arylation polymerization (DArP) to give donor− acceptor type alternating copolymers (DA polymers) with unsubstituted 2,2′-bithiophene units. When only L1 is used as a ligand, the reaction of 5,6-difluoro-4,7-bis) in toluene at 100 °C forms a notable amount of insoluble materials via branching and cross-linking. In contrast, in the presence of L1 and TMEDA, the formation of insolub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 36 publications
0
36
0
Order By: Relevance
“…These phenylene and naphthalene polymers are prepared by Suzuki or Stille couplings, but there are some recent examples of dialkoxyphenylene-based polymers successfully synthesized by DAP with high molecular weight [40][41][42][43]. These examples added to the significant advances made in preparing well-defined conjugated polymers via DAP [44][45][46][47][48][49][50][51][52], open the door to produce CPs based on 2,3-dialkoxynaphthalene.…”
Section: Introductionmentioning
confidence: 99%
“…These phenylene and naphthalene polymers are prepared by Suzuki or Stille couplings, but there are some recent examples of dialkoxyphenylene-based polymers successfully synthesized by DAP with high molecular weight [40][41][42][43]. These examples added to the significant advances made in preparing well-defined conjugated polymers via DAP [44][45][46][47][48][49][50][51][52], open the door to produce CPs based on 2,3-dialkoxynaphthalene.…”
Section: Introductionmentioning
confidence: 99%
“…Ozawa et al first developed a "mixed ligand catalyst" approach and found that the combined use of L1 and an affordable tetramethylethylenediamine (TMEDA) ligand effectively suppressed the formation of branching defects and significantly reduces the homocoupling defects resulting from debromination events. 163,164 The synthesis of TPD-based copolymer P21 via DArP was first examined by Leclerc et al, 165 who reported the formation of insoluble material, an indication of potential branching and crosslinking defects embedded in the polymer structure. Ozawa et al attempted the reaction at a lower temperature (decreased from 120 to 100 C) with a different Pd catalyst (changed from Pd 2 (dba) 3 ÁCHCl 3 to Pd(Herrmann)) while the ligand of choice remained the same (L1); however, 74% of the polymer product was isolated as insoluble materials while the soluble portion of the product contained a large amount of defects, as determined by 1 H NMR analysis.…”
Section: Suppression Of Defect-formation In Ozawa-derived Darp Methodsmentioning
confidence: 99%
“…46,47 DArP has emerged as a promising and greener synthetic strategy for defect-free D-A copolymers, in contrast to the conventional coupling methods. [48][49][50] Synthesizing D-A copolymers via conventional coupling methods can be difficult because the pre-functionalization to prepare the required electron-poor comonomers is challenging due to either their unresponsiveness to electrophilic substitution or their decomposition during the functionalization reactions. [51][52][53] In this case, DArP, where C-H activation of one of the comonomers is a crucial part, appears to be a favorable synthetic method for D-A copolymers.…”
Section: Recent Advances In Developing Alternative Synthetic Methodsmentioning
confidence: 99%
“…Recently, Ozawa et al also reported some syntheses of D-A copolymers with well-defined structures using DArP. 49,50 They prepared a D-A copolymer using 1,2dithienylethene (DTE) (donor) and dibromoisoindigo (acceptor) as comonomers and a catalytic system consisting of Pd 2 (dba) 3 Á CHCl 3 , P(2-MeOC 6 H 4 ) 3 , pivalic acid, and Cs 2 CO 3 . 49 The resulted D-A copolymer exhibited a high molecular weight (M n was up to 44.9 kg mol À1 ) and less than 0.1% homocoupling defect.…”
Section: Recent Advances In Developing Alternative Synthetic Methodsmentioning
confidence: 99%
See 1 more Smart Citation